The profile of extremity and trunk soft tissue sarcoma in a tertiary referral center - Ahmed Mostafa Ahmed Mahmoud; Mohammed Mahmoud; Ahmed Charaf; Manar Mohamed Moneer (Journal of the Egyptian National Cancer Institute, 2017)
Background: Proper surgery with adequate safety margin and adjuvant radiotherapy is the main line of treatment of extremity and trunk soft tissue sarcoma (STS). In spite of improved management, the long term follow up is still not satisfactory. Objective: To evaluate long term outcome of STS of extremities and trunk regarding adequacy of resection, recurrence and survival. Patients and methods: This prospective study included 25 patients with STS involving extremity and trunk. All patients were treated with wide radical excision and had adjuvant irradiation and followed up for a median of 26 months. Results: The mean age was 40.0 ± 15.3 years. They were 16 males and 9 females. Eight patients (32%) had positive or close surgical margins. The median overall survival (OS) was 26.5 months. In univariate analysis, lower limb tumors, stage III and grade 3 were significantly associated with worse overall survival (OS) (p = 0.007, 0.02, and 0.020, respectively) and disease free survival (DFS) (p = 0.005, 0.001, and 0.001, respectively). On multivariate analysis the only independent factor that affects the OS and DFS was the stage (p value = 0.029, Hazard ratio: 3.64, 95% confidence interval: 1.14–11.61 and p value = 0.003, Hazard ratio: 5.75, 95% confidence interval: 1.82–18.18 respectively). Conclusion: Despite adequate surgery and adjuvant irradiation, 5 years follow up results of treatment of extremity and trunk soft tissue sarcoma is still poor. This highlights the importance of early detection of small STS in extremity and trunk.